Self regulated learning of prospective mathematics teacher in solving linier program problem: a case of visual learning style - A A Nugroho; D Juniati; T Y E Siswono (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research is to knowing self-regulated learning of the prospective mathematics teacher with visual learning style in solving math problem. Self-regulated learning ability of a teacher or prospective mathematics teacher in solving math problem is too important to increase self-regulated learning of the students in solving math problem. The data collected by self-regulated learning questionnaire, problem solving test in mathematics and semi structured interview from prospective mathematics teacher with a visual learning style at Universitas PGRI Semarang. The result showed that the subject of self-regulated learning ability in solving math problem in planning stage, forethought and activation of the subject have understanding of a problem, can identify the information that appears on the problem and can estimate the completion and procedure required. At the stage of monitoring the subject does monitoring activities in the process of solving the problem. At the control stage the subject control in the process of solving the problem. At the reaction and reflection stage the subject does an evaluation in solving the problem.